Peningkatan Mutu Pendidikan Karakter Sebagai Strategi Mengatasi Tantangan Kebangsaan - I Ketut Tanu; I Nengah Juliawan (UHN IGB Sugriwa Denpasar, 2020)
Education is an orderly system and has a fairly broad mission, namely everything that is related to physical development, health, skills, thoughts, feelings, wills, social to issues of belief or faith. This shows that school as a formal educational institution has a heavy load in carrying out the educational mission. This is especially so if it is related to the rapid changes of the times these days which greatly affect students in thinking, behaving and behaving, especially those who are still in a stage of development in transition who are looking for self-identity. In terms of character education, the Indonesian nation really needs large and quality human resources (human resources) to support the implementation of development programs properly. This is where quality education is needed, which can support the achievement of the nation's ideals of having quality resources, and in discussing quality human resources and their relationship with education, what is assessed first is how high the value it often gets, in other words quality. measured by numbers, so it is not surprising that in order to pursue the targets set by an educational institution, it sometimes commits fraud and manipulation.